2021
DOI: 10.1016/j.xkme.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium and Cardiovascular Outcomes and Mortality in CKD: The Chronic Renal Insufficiency Cohort (CRIC)

Abstract: Rationale & Objective Low serum magnesium level has been shown to be associated with increased mortality, but its role as a predictor of cardiovascular disease is unclear. This study evaluates the association between serum magnesium level and cardiovascular events and all-cause mortality in a large cohort of individuals with chronic kidney disease (CKD). Study Design Prospective cohort study. Setting & Participants 3,867 participants with CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…In line with this, a prospective cohort study in 5044 participants demonstrated a nonlinear relationship of serum magnesium with diabetes and insulin resistance 47 . On the other hand, Negrea et al found that serum magnesium <1.9 mg/dL and >2.1 mg/dL was associated with all‐cause mortality in a large cohort of patients with CKD 48 …”
Section: Discussionmentioning
confidence: 83%
“…In line with this, a prospective cohort study in 5044 participants demonstrated a nonlinear relationship of serum magnesium with diabetes and insulin resistance 47 . On the other hand, Negrea et al found that serum magnesium <1.9 mg/dL and >2.1 mg/dL was associated with all‐cause mortality in a large cohort of patients with CKD 48 …”
Section: Discussionmentioning
confidence: 83%
“…Here we show that GRP serum levels are positively associated with Mg, a known vascular calcification inhibitor [ 34 , 35 ]. The importance of P and Mg in vascular calcification and cardiovascular risk have been extensively demonstrated at both epidemiological and mechanistic levels, both in the general population and CKD, with hyperphosphatemia and hypomagnesia associated with increased vascular calcification, cardiovascular events and mortality [ 34 , 35 , 36 , 37 , 38 , 39 ]. In relation to VC, hyperphosphataemia has been associated with aortic and mitral valves calcification, including in moderate CKD patients [ 12 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Lastly, in patients with CKD, in the multiethnic DHS (Dallas Heart Study) cohort, over 12.3 years median follow-up, low serum magnesium (<0.8 mmol/L) was independently associated with all-cause mortality 13 ; and more recently, an analysis from CRIC demonstrated that serum magnesium levels <1.9 mg/dL and >2.1 mg/dL were associated with an increased risk of all-cause mortality. 35 Multiple mechanisms may explain the associations between magnesium and CVD. Magnesium antagonizes voltage-dependent L-type calcium channels in vascular smooth muscles cells, thereby inhibiting calcium influx and leading to reduced vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…15 Lastly, in patients with CKD, in the multiethnic DHS (Dallas Heart Study) cohort, over 12.3 years median follow-up, low serum magnesium (<0.8 mmol/L) was independently associated with all-cause mortality 13 ; and more recently, an analysis from CRIC demonstrated that serum magnesium levels <1.9 mg/dL and >2.1 mg/dL were associated with an increased risk of all-cause mortality. 35…”
Section: Discussionmentioning
confidence: 99%